Alcohol and Drug Overdose and the Influence of Pain Conditions in an Addiction Treatment Sample. Issue 1 (January 2019) - Fernandez, Anne C.; Bush, Christopher; Bonar, Erin E.; Blow, Frederic C.; Walton, Maureen A.; Bohnert, Amy S.B.
Abstract : Purpose: Overdose from alcohol and/or drugs kills tens of thousands of Americans annually, with a large number of deaths attributed to opioid pain medications. Addiction treatment patients are known to be at high risk for overdose; however, the relationship between pain and overdose history within this group is understudied, especially in relation to alcohol overdoses. In the present study, we evaluated whether nonfatal overdose history was more likely among addiction treatment patients with pain, and examined the characteristics of overdoses among those with and without pain. Methods: We analyzed cross-sectional data from 739 patients at a large residential addiction treatment center (median age 37, 25.7% female). We used 2-stepped binary regression models to evaluate whether demographics, pain type (chronic, acute, or both), depression symptoms, and opioid misuse were associated with lifetime history of nonfatal (1) alcohol and (2) drug overdose (lifetime yes/no), and conducted follow-up analyses examining overdose characteristics. Results: In adjusted analyses, history of chronic pain (odds ratio [OR] 2.60, 95% confidence interval [CI] 1.59, 4.27) and illicit drug use (OR 1.99, 95% CI 1.07, 3.68) were associated with an increased likelihood of nonfatal alcohol overdose. Opioid misuse (OR 3.11, 95% CI 2.51, 3.86), depression symptoms (OR 1.33, 95% CI 1.14, 1.55), and younger age (OR 0.96, 95% CI 0.94, 0.97) were associated with increased likelihood of drug overdose. Those with pain reported a higher number of lifetime alcohol overdoses and were more likely to combine numerous drugs with alcohol before overdose. Conclusions: Pain conditions may play an under-recognized role in the overdose epidemic, particularly alcohol-related overdose. Addiction treatment and overdose prevention interventions should incorporate appropriate assessment and treatment of pain including education about the risks of polysubstance use, particularly combining alcohol with sedatives and prescription pain relievers.